A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Diversification of mitogenomes in three sympatric Altica flea beetles (Insecta, Chrysomelidae) - Rui‐E Nie; Jing Wei; Shou‐Ke Zhang; Alfried P. Vogler; Ling Wu; Alexander S. Konstantinov; Wen‐Zhu Li; Xing‐Ke Yang; Huai‐Jun Xue (Zoologica Scripta, 2019)
The Asian flea beetles Altica cirsicola , Altica fragariae and Altica viridicyanea are broadly sympatric and morphologically highly similar but feed on distantly related host plants. They have been suggested as a model for ecological speciation studies. However, their phylogeny and species limits remain uncertain. In this study, we added mitochondrial genomes from multiple individuals of each species to the growing database. Phylogenetic analyses based on 15 genes showed clear interspecific divergences of A. fragariae from the other species, but A. cirsicola and A. viridicyanea were not distinguishable by distance‐based or tree‐based methods of species delimitation due to non‐monophyly of mitogenomes relative to the morphologically defined entities, possibly affected by interspecific introgression. This was confirmed by wider sampling of mitochondrial COX1 (58 individuals) and the second internal transcribed spacer of nuclear ribosomal RNA cluster (ITS2; 68 individuals), which showed that ITS2, but not COX1, coincided with the morphological species limits. The full mitochondrial genomes are not able to shed further light on the species status, even with the most sensitive approach based on diagnostic characters, yet the whole mitogenome is useful to get improved estimates of intra‐ and interspecific variation, not affected by the stochastic error seen in individual genes.

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.